The influence of college students’ sense of life meaning on psychological well-being: The mediating roles of positive emotions and life adaptation - Zang, Weiyu; Zhang, Cangkai (Nurture, 2024)
Purpose: This study aims to investigate the factors influencing the sense of life meaning and psychological well-being among college students and to understand and explore the mediating roles of positive emotions and life adaptation. Design/Methodology/Approach: This study used a quantitative approach for testing. A total of 1,152 college students were randomly selected from nine higher education institutions located in Shanxi Province, China. Findings: There is a positive relationship between college students’ sense of life meaning and psychological well-being. Positive emotions and life adaptation play a mediating role in the relationship between college students’ sense of life meaning and psychological well-being. Conclusion: College students’ sense of life meaning exerts a mediating effect on psychological well-being through life adaptation. Positive emotions and life adaptation also mediate the effects of a sense of life meaning on psychological well-being. Research Limitations/Implications: The sample in this study was exclusively drawn from various higher education institutions in Shanxi Province, China. Therefore, the conclusion may not be universally applicable to all levels of education and teaching situations. Practical Implications: This study provides valuable insights for schools and society to formulate targeted measures for promoting psychological health thereby enhancing college students’ life satisfaction and happiness. Contribution to the Literature: This research establishes a structural framework for understanding the relationship between positive emotions, life adaptation and psychological well-being providing an important reference for future studies in this area.